Slovenski kineziološki termini s pridevniško sestavino gibalni ali motorični in njihovi angleški ustrezniki - Jurša, Barbara (Slovenski jezik, 2025)
The paper examines Slovenian kinesiological multiword terms containing either the adjectival element gibalni or motorični as a noun premodifier based on their occurrence in terminological dictionaries and scientific and professional texts in the subject field of kinesiology. By comparing the relevant entries in Slovenian and English terminological dictionaries and examining bilingual abstracts from Slovenian kinesiological journals, the study attempts to determine the English equivalents of these terms. However, the overall aim is to contribute to greater clarity and trans-parency of the Slovenian scientific language in kinesiology, by noting examples of inconsistent use of terms.
Keywords: angleški jezik; English language; kinesiology; kineziologija; multiword terms; prevajanje; terminological variation; terminološka variantnost; večbesedni termini